Inhibitory effects of isatin Mannich bases on carbonic anhydrases, acetylcholinesterase, and butyrylcholinesterase. (1st November 2016) - Ozgun, Dilan Ozmen; Yamali, Cem; Gul, Halise Inci; Taslimi, Parham; Gulcin, Ilhami; Yanik, Telat; Supuran, Claudiu T.
Abstract: The effects of isatin Mannich bases incorporating (1-[piperidin-1-yl (P1 )/morpholin-4-yl (P2 )/ N -methylpiperazin-1-yl (P3 )]methyl)-1 H -indole-2, 3-dione) moieties against human (h) carbonic anhydrase (CA, EC 4.2.1.1) isoenzymes hCA I and hCA II, acetylcholinesterase( AChE), and butyrylcholinesterase (BChE) enzymes were evaluated.P1 –P3 demonstrated impressive inhibition profiles against AChE and BChE and also inhibited both CAs at nanomolar level. These inhibitory effects were more powerful in all cases than the reference compounds used for all these enzymes. This study suggests that isatin Mannich basesP1–P3 are good candidate compounds especially for the development of new cholinesterase inhibitors since they were 2.2– 5.9 times better inhibitors than clinically used drug Tacrine.